Spatially resolved studies of the phases and morphology of methylammonium and formamidinium lead tri-halide perovskites. Issue 9 (22nd February 2017) - Galkowski, K.; Mitioglu, A. A.; Surrente, A.; Yang, Z.; Maude, D. K.; Kossacki, P.; Eperon, G. E.; Wang, J. T.-W.; Snaith, H. J.; Plochocka, P.; Nicholas, R. J.
Abstract : Local photoluminescence measurements of organic–inorganic tri-halide perovskites show a temperature dependent crystal domain structure closely related to device performance. Abstract : The family of organic–inorganic tri-halide perovskites including MA (MethylAmmonium)PbI3, MAPbI3− x Cl x, FA (FormAmidinium)PbI3 and FAPbBr3 are having a tremendous impact on the field of photovoltaic cells due to the combination of their ease of deposition and high energy conversion efficiencies. Device performance, however, is known to be still significantly affected by the presence of inhomogeneities. Here we report on a study of temperature dependent micro-photoluminescence which shows a strong spatial inhomogeneity related to the presence of microcrystalline grains, which can be both bright and dark. In all of the tri-iodide based materials there is evidence that the tetragonal to orthorhombic phase transition observed around 160 K does not occur uniformly across the sample with domain formation related to the underlying microcrystallite grains, some of which remain in the high temperature, tetragonal, phase even at very low temperatures. At low temperature the tetragonal domains can be significantly influenced by local defects in the layers or the introduction of residual levels of chlorine in mixed halide layers or dopant atoms such as aluminium. We see that improvements in room temperature energy conversion efficiency appear to be directly related to reductions in the proportions of the layer which remain in the tetragonal phase at low temperature. In FAPbBr3 a more macroscopic domain structure is observed with large numbers of grains forming phase correlated regions.